PERAN BAHASA ARAB DALAM MEMAHAMI PENDIDIKAN AGAMA ISLAM DENGAN PENDEKATAN BERFIKIR KNOWLEDGE OR CERTAINTY - MIFTAH WANGSA DANUREJA (Universitas Muhammadiyah Prof Dr Hamka, 2017)
Islamic Education (PAI) becomes one of the subjects that must be held in every college. In fact the course of PAI in college has some problems, one of which is the difficulty students in understanding the materials contained in the PAI subjects, especially in understanding terms in Arabic. Therefore, we need a new approach to teach PAI. One of the new approaches is the need of understanding Arabic Terms. To reach this purpose we need a new activity like Arabic terms translation on every material contained in PAI Subject. This could help students' understanding. The writer makes a new learning concept that is Arabic terms translation using Thinking Approach based on Knowledge or Certainty. The aims of this study are 1). To know whether the understanding of Arabic terms can affect the understanding of the PAI. 2) to know the influence of the Arabic translation methods upon the understanding of PAI. After the results of the correlation coefficient significance test data showed that the double correlation coefficient (Ry.12) = 0.785 and Fhit (Fchange) = 16 881, and p-value = 0.000 <0.05 or H0 is rejected. Thus, the multiple correlation coefficient between X1 and X2 with Y is meaningful or significant. While the coefficient of determination shown by R Square = 0.617, so it can be concluded that the influence of the Arabic language with knowledge or Certainty thinking approach with the same towards the understanding of the subjects PAI amounted to 61.7%.